Heteropolyanions Catalysts for n-Heptane Conversion: Effect of the Counter Cation and the Addenda Atoms - Aouissi, Ahmed; Al-Dhayan, Daif; Abdullah Al-Othman, Zeid; Lokbaichi, Ahmed (Asian Journal of Chemistry, 2012)
Different heteropoly compounds (HPC) H3PW12O40, H3PMo12O40, H4PMo11VO40 and Cu1.5PMo12O40 were prepared and characterized by means of FTIR and thermogravimetry. Their catalytic properties for the n-heptane reaction were evaluated at 300 ºC. In this study the effect of the addenda atoms (W, Mo and V) and the counter cations (H+ and Cu2+) was investigated. The substitution of W atoms with Mo ones increased the conversion and favoured the cracking selectivity to the detriment of that of cyclization while isomerization selectivity remained unchanged. When the protons were replaced with copper ions, cracking and cyclization reactions were favoured to the detriment of that of isomerization. Heteropolyacids have been found more active than the copper heteropolymolybdate salt. Increasing hydrogen pressure favoured cyclization and cracking reactions to the detriment of isomerization one.